MUHAMMAD RIZA AGOHIY IS A GREAT REPRESENTATIVE OF KHORAZM HISTORICAL SCHOOL - Durdona Mashrbaliyeva (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides brief information about the life, work, and scientific heritage of the historian and statesman Muhammad Reza Agohi. In particular, Agohi’s contribution to the Khorezm school of historiography, his historical works, and their importance are highlighted.